Hubungan Konsumsi Protein dengan Kadar Hemoglobin Remaja Putri di Kabupaten Bekasi - Putri Nur Hidayah; Nur Fauzia Asmi; Utami Putri Kinayungan; Dandi Sanjaya (Universitas Muhammadiyah Manado, 2025)
Hemoglobin plays a vital role in transporting oxygen throughout the body. A decrease in hemoglobin levels can lead to oxygen deficiency in tissues, potentially causing anemia. Anemia is characterized by symptoms such as fatigue, dizziness, and reduced concentration, and is a health issue that must be addressed, especially among adolescent girls. This is a quantitative study using an analytical observational method with a cross-sectional design. The study population consisted of 516 female students aged 15–18 years at SMAN 3 Cikarang Utara, with 92 students selected as samples using purposive sampling. The research was conducted in June 2025. Data analysis was performed using the chi-square test. The findings revealed that 33 students (35.9%) experienced anemia out of the 92 participants. Furthermore, 45 students (48.9%) had inadequate protein intake, 39 students (42.4%) engaged in heavy physical activity, and 37 students (40.2%) were categorized as food insecure. Significant associations were found between protein intake (p = 0.000), physical activity (p = 0.000), and household food security (p = 0.047) with hemoglobin levels in adolescent girls. There is a relationship between protein intake, physical activity, and household food security with hemoglobin levels among adolescent girls.